Integrating Urban Adolescent Mental Health Into Urban Sustainability Collective Action: An Application of Shiffman & Smith’s Framework for Global Health Prioritization - Murphy, Lauren E.; Jack, Helen E.; Concepcion, Tessa L.; Collins, Pamela Y. (Frontiers in Psychiatry, 2020)
The majority (55%) of the world’s population lives in urban environments. Of relevance to global mental health, the rapid growth in urban populations around the world and the attendant risks coincide with the presence of the largest population of adolescents the global community has seen to date. Recent reviews on the effects of the urban environment on mental health report a greater risk of depression, anxiety, and some psychotic disorders among urban dwellers. Increased risk for mental disorders is associated with concentrated poverty, low social capital, social segregation, and other social and environmental adversities that occur more frequently in cities. To address these problems, urban adolescent mental health requires attention from decision makers as well as advocates who seek to establish sustainable cities. We examine opportunities to increase the prominence of urban adolescent mental health on the global health and development agenda using Shiffman and Smith’s framework for policy priorities, and we explore approaches to increasing its relevance for urban health and development policy communities. We conclude with suggestions for expanding the community of actors who guide the field and bridging the fields of mental health and urban development to meet urban adolescent mental health needs.